Pemanfaatan Media Sosial Instagram untuk Meningkatkan Pengetahuan Remaja Tentang Pubertas - Hariyani Sulistyoningsih; Sinta Fitriani, S.KM., M.K.M (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Adolescents need accurate information about puberty, because adolescents who fail to go through the puberty phase may experience psychological disorders that have an impact on the next phase of life. This service activity is carried out to disseminate information on puberty by utilizing Instagram media. The specific purpose of this activity is to make adolescents understand the definition of puberty, when puberty occurs, changes that generally occur during puberty and the correct attitude in dealing with puberty. The method is the delivery of material directly through social media. Activities carried out in three stages, namely: planning, implementation and reflection. Planning includes material preparation and socialization of activities; implementation includes the delivery of information through live broadcasts using Instagram, starting with the presentation of the material, followed by answering questions. The last stage is reflection, namely analyzing the responses of the participants. Participants responded very well, as evidenced by a number of questions and statements of support that were delivered during the activity. Dissemination of information for adolescents as well as parents through online media needs to continue, especially during the period of limiting activities due to the pandemic.